Pacing profiles and performance in 800 m meeting races during a new technological era: Influence of wavelight technology - González-Mohíno, F.; Rodríguez-Barbero, S.; Gómez, M.; Salinero, J. S. (Applied Sciences, 2026)
Background: Wavelight technology (WT) has recently been introduced in international track meetings as a pacing aid designed to enhance consistency and performance. This study aimed to analyze the influence of WT on mean race speed and pacing profiles in 800 m Diamond League (DL) races and to compare its effects between men and women.